2021
DOI: 10.3390/agriculture11090877
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Analysis of Traditional Post-Harvest Operation Methods and the Loss Reduction Effect Based on Five Time (5T) Management: The Case of Rice in Jilin Province, China

Abstract: Traditional post-harvest operation methods applied in rice fields lack advanced management knowledge and technology, which has led to post-harvest losses. We proposed the concept of Five Time (5T) management for the first time. 5T management divides the whole life cycle of rice into different growth time interval to complete process management. This paper mainly introduces the management of rice grain period, that is, the post-harvest management period, including the operation process management of harvesting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Although different scholars have extensively discussed and studied the post-harvest losses of grain, they mainly focus on its characteristics and evaluation methods [22][23][24][25], and pay less attention to the post-harvest latent losses and the possibility of participating in timely rice harvest determination. In 2019, we conducted a 5 T management experiment on the harvesting and storage of three high-quality rice varieties [26]. Our experimental results showed that the dry matter of the rice grains reached its peak on a certain day of the rice maturity period and began to decrease over time, which we call latent loss.…”
Section: Introductionmentioning
confidence: 97%
“…Although different scholars have extensively discussed and studied the post-harvest losses of grain, they mainly focus on its characteristics and evaluation methods [22][23][24][25], and pay less attention to the post-harvest latent losses and the possibility of participating in timely rice harvest determination. In 2019, we conducted a 5 T management experiment on the harvesting and storage of three high-quality rice varieties [26]. Our experimental results showed that the dry matter of the rice grains reached its peak on a certain day of the rice maturity period and began to decrease over time, which we call latent loss.…”
Section: Introductionmentioning
confidence: 97%
“…Rice provides up to 50% of the dietarycaloric supply and a substantial part of the protein intake for about 520 million people living in poverty in Asia 2 . The market value of rice is primarily determined by the grain quality, which in turn depends on the genetic background, agronomic management, geographic factors and postharvest factors 3 , 4 . Although the grain quality and thus the price for rice of different geographic origins could differ vastly, their appearance may be very alike.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, grain loss is significant because of inadequate post-harvest management knowledge and technology, improper storage facilities, and other factors. Around 20-30% losses of grains are recorded from most of the African countries [2]; and further 10 to 30% to other parts of the world [3]. Before storage of seeds, drying is a widely explored method for longer shelf life of agricultural products [4].…”
Section: Introductionmentioning
confidence: 99%